Driver Visual Processing of Relevant and Irrelevant Information During Mind Wandering. (December 2020) - Wagner, Richard B.; Geden, Michael; Forster, Sophie; Feng, Jing
Mind wandering is a common phenomenon in our daily lives, especially in routine tasks such as driving familiar routes. Some evidence suggests that there are detrimental effects of mind wandering on driving performance, but limited research has been conducted to examine the influence of mind wandering on a driver's attentional processing of relevant or irrelevant information. More specifically, it is unclear as to whether the effects of mind wandering depend on the task relevancy of information presented in the visual field. The current study expands literature on mind wandering during driving using eye tracking to measure driver visual processing of relevant/irrelevant signage information in a simulated driving task while drivers reported their mental states. Preliminary results showed no significant differences in frequency and duration of glances to roadway information based on the mental state of the individual as well as the task relevancy of the information. Implications and future directions are discussed.